THỜI TIẾT MƯA LỚN VÀ QUAN HỆ CỦA MƯA LỚN, MƯA LŨ, DÒNG CHẢY, CÁT BÙN Ở VÙNG GÒ ĐỒI THANH - NGHỆ - Vân, Nguyễn Khanh; Lan, Vũ Thị Thu (Vietnam Journal of Earth Sciences, 2017)
Based on meteorological, hydrological data and analysis weather situations causing heavy and veryheavy rains, inundation, floods over Hieu river basin, there are some conclusions as follow :In July heavy rains causing inundation are activities of weather situations like baric trough in low area of troposphere or cyclone in high area of troposphere in corporation with strong south-eastwind ; In August - typhoons and cyclones ; In September - typhoons, cyclones or typhoons incorporation with cold air mass going after coldfront; In October - tropical depression inintertropical convergence zone corporation withcold air mass going after cold front of anticyclone incorporation with strohg south-east wind ; In November - intensive cold air mass going aftercold front in cooperation with typhoons in the south.The heavy rain plays an important role in forming crest of a flood . In the Hieu basin, the correlated coef ficient between heavy rain and crest of a flood reaches over 0.8. Froni the other side, the heavy rain plays an important role forestablishing the sand muddy flow on the river. The highest rainfall during the day influences eroding the surface of the long dry season area, which shows clearly comparing with humid area the shortdry season. In addition, the highest rainfall during the day relates closely to the turbidity of the river with large basin and with sediment of the river with small basin.We hope our study conclusions will help prevent and reduce the damage of natural calamities.